Self-renewal : high performance in a high-stress world - Jaffe, Dennis (Crisp Pub. Menlo ParkUS, 1994)
Explores some of life's hassles e.g. conflict with others, life change, loss; and suggests strategies for creating the personal power needed for coping. Strategies include: making changes in small steps; rewarding oneself for each accomplishment; and, finding a support person. Stresses the need for getting help and support from positive, helpful and self-supporting relationships. Shows how application techniques e.g. relaxation and meditation, can reduce stress and lead to better health.